Kepemimpinan Otentik dan Iklim Organisasi terhadap Produktivitas Pegawai: Peran Mediasi Komitmen Afektif pada Kantor Imigrasi Kelas I TPI Balikpapan - Januar Yudistiawan Manan; Mashur Razak; Muh. Ashary Anshar (Fakultas Ekonomi dan Bisnis, Universitas Muslim Indonesia, 2026)
This study examines the effects of authentic leadership and organizational climate on employee productivity, with affective commitment as a mediating variable, at the Class I Immigration Office of TPI Balikpapan. The study is relevant because immigration agencies must maintain service speed and accuracy while simultaneously meeting surveillance, procedural compliance, and increasing performance targets. A quantitative explanatory survey was conducted using a saturated sample of all 138 employees. Data were collected through a five-point Likert questionnaire and analyzed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with SmartPLS 4. The findings show that authentic leadership positively affects affective commitment (β = 0.403; p < 0.001) and productivity (β = 0.223; p = 0.001). Organizational climate also positively affects affective commitment (β = 0.396; p < 0.001) and productivity (β = 0.290; p < 0.001). Affective commitment positively affects productivity (β = 0.364; p < 0.001) and partially mediates the effects of authentic leadership (indirect β = 0.147; p = 0.001) and organizational climate (indirect β = 0.144; p < 0.001) on productivity. The model explains 50.7% of the variance in productivity and demonstrates moderate predictive relevance (Q² = 0.356). The results indicate that productivity in public service organizations is not sustained by formal direction alone; it improves when consistent leadership behavior and a supportive organizational climate develop employees’ emotional attachment to the institution.